2003
DOI: 10.1099/vir.0.18695-0
|View full text |Cite
|
Sign up to set email alerts
|

RNase L activity does not contribute to host RNA degradation induced by herpes simplex virus infection

Abstract: In early herpes simplex virus (HSV) infection, the virion host shutoff (vhs) protein mediates the degradation of mRNA and subsequent shutoff of host protein synthesis. It is unclear whether vhs acts alone or in concert with virus-induced cellular factors for this activity. This paper examines whether RNase L, a virally induced endoribonuclease, contributes to HSV-induced mRNA decay. Results showed that RNA degradation was comparable in wild-type and RNase L 2/2 cells, demonstrating that HSV-mediated RNA degrad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
6
0

Year Published

2004
2004
2009
2009

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 31 publications
2
6
0
Order By: Relevance
“…However, we demonstrated that the RNase L pathway is only modestly activated during the time course of the VZV infection. The rRNA cleavage assay showed almost no 28S and 18S rRNA cleavage, indicating that VZV is a poor inducer of RNase L in vitro, as is also the case for HSV-1 [7,20]. In VZV-infected, IFN-treated cells, minor rRNA cleavage products were observed to a greater extent than in nontreated cells.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…However, we demonstrated that the RNase L pathway is only modestly activated during the time course of the VZV infection. The rRNA cleavage assay showed almost no 28S and 18S rRNA cleavage, indicating that VZV is a poor inducer of RNase L in vitro, as is also the case for HSV-1 [7,20]. In VZV-infected, IFN-treated cells, minor rRNA cleavage products were observed to a greater extent than in nontreated cells.…”
Section: Discussionmentioning
confidence: 83%
“…Until recently, it was unclear whether the vhs protein acts alone or as a part of a ribonuclease complex, or whether it activates a latent cellular RNase such as RNase L. Smith et al [20] demonstrated that RNase L does not contribute to host RNA degradation mediated by the HSV vhs protein. We have reported that VZV does not cause a rapid shutoff like HSV but a delayed vhs effect during its replication cycle [21].…”
Section: Discussionmentioning
confidence: 98%
“…However, since the stability of ␤-actin mRNA was not differentially affected by infection with wt HSV-1 versus in1814, RNase L appears not to be a likely candidate. Moreover, a recent study demonstrated that HSV-1 does not activate RNase L and that mRNA degradation in HSV-infected cells is independent of RNase L (41). The HSV tegument protein UL41 (or VHS), which promotes mRNA degradation, has previously been shown to decrease accumulation of some virus-induced cellular mRNAs (44), although the majority of cellular genes induced by HSV-1 infection are not affected by UL41 (45).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, only low levels of RNase L-mediated rRNA cleavage products were observed, despite the fact that RNase L is typically highly activated by similar levels of 2-5A in IFN-treated EMCV-infected cells. RNase L also has little or no effect on host RNA degradation mediated by VHS, the HSV-1 virion host shutoff protein, in MEFs (111). A possible explanation for the relative inactivity of RNase L in HSV-infected cells emerged from analysis of the types of 2-5A species produced.…”
Section: Poxviridaementioning
confidence: 99%